Germany : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2000)
The conceptual framework of this paper assumes that macroeconomic performance depends on the interplay between the economic environment and policies. Declining labor shares, wage moderation, and employment performance in Germany and the Netherlands have been presented. A number of policy changes are under way, but additional reforms may be needed to fully reap the benefits of the new economy. The tax reform package marks a radical and constructive shift in German tax policy, and the pension system requires a sea of change in public policy reforms.